2022
DOI: 10.1002/admt.202200645
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ternary Nitride Thin Film‐Based Self‐Powered, Broad Spectral Responsive Photodetector with a High Detectivity for Weak Light

Abstract: with titanium nitride (TiN) as the most common example. [1] Along with their superior mechanical properties, these are good conductors being employed as permanent contact layers and diffusion barriers in microelectronics. [1] In addition, nitrides are well explored as novel piezoelectric and thermoelectric materials, generally in the area of energy harvesting (e.g., aluminium nitride (AlN)). AlN has been well studied in the past 20 years due to its excellent properties, such as wide bandgap, high thermal condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
(107 reference statements)
1
10
0
Order By: Relevance
“…For example, the thickness of the Mo-incorporated Cu 2 ZnSnS 4 absorber layer increased with Mo cosputtering power, as shown in the cross-section scanning transmission electron microscope study . More recently, the ternary metal–zinc–nitride thin films of about 235 nm thickness were demonstrated experimentally and implemented in a photodetector device . Proper choice of a substrate is an important step for production of 2D Zn 2 VN 3 .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…For example, the thickness of the Mo-incorporated Cu 2 ZnSnS 4 absorber layer increased with Mo cosputtering power, as shown in the cross-section scanning transmission electron microscope study . More recently, the ternary metal–zinc–nitride thin films of about 235 nm thickness were demonstrated experimentally and implemented in a photodetector device . Proper choice of a substrate is an important step for production of 2D Zn 2 VN 3 .…”
mentioning
confidence: 91%
“…25 More recently, the ternary metal−zinc−nitride thin films of about 235 nm thickness were demonstrated experimentally and implemented in a photodetector device. 26 Proper choice of a substrate is an important step for production of 2D Zn 2 VN 3 . For instance, bulk Zn 2 VN 3 deposited on glass and sapphire substrates appears to be phase-pure, while the epitaxial stabilization on Al 2 O 3 (0001) increases its crystallinity and texture.…”
mentioning
confidence: 99%
“…In contrast, the CPD Au and CPD sample are the contact potential differences between the gold tip and the gold reference surface and between the gold tip and the sample, respectively. [40,81] The hemolysis assay was performed to investigate the influence of single-phase Ti 0.5 Zn 0.5 compound on human cells and their ability to induce cytotoxicity. For hemolysis assay, the blood samples were acquired intravenously from a healthy male donor containing normal counts of RBC cells into ethylenediamine tetraacetic acid vials (SRM Medical College Hospital and Research Centre, Chengalpattu, Tamil Nadu, India).…”
Section: Methodsmentioning
confidence: 99%
“…26 A ITO/TiZnN 2 /Si photodetector has been developed generating a photocurrent with a low light intensity and insensitive to humidity. 27 It has also been shown that Zn 2 V (1−x) Nb x N 3 alloys possess comparably small bowing parameter that is beneficial for materials used in light-emitting diodes. 28 Another important question regarding the performance of tandem solar cells is related to the environmental stability of the top layer based on ternary nitrides.…”
mentioning
confidence: 99%
“…A ZnSnN 2 thin film has been utilized as an absorbing material is solar cells, with the ZnSnN 2 / p -CuCrO 2 solar cell exhibiting an efficiency exceeding 22% . A ITO/TiZnN 2 /Si photodetector has been developed generating a photocurrent with a low light intensity and insensitive to humidity . It has also been shown that Zn 2 V (1– x ) Nb x N 3 alloys possess comparably small bowing parameter that is beneficial for materials used in light-emitting diodes …”
mentioning
confidence: 99%